A Prospective Study on the Efficacy of Cognitive Targeted Transrectal Ultrasound Prostate Biopsy in Diagnosing Clinically Significant Prostate Cancer - Thangarasu, Mathisekaran (Res Rep Urol, 2021)
PURPOSE: We present our study, done to identify the diagnostic yield of cognitive targeted biopsy using mpMRI data, to diagnose clinically significant prostate cancers, in a cohort of biopsy and treatment naive men. MATERIALS AND METHODS: This is a prospective, single institutional study, done from September 2018 to March 2020 in 75 biopsy naive men. The patients with 3, 4 and 5 PIRADS scores underwent mpMRI cognitive target biopsy (mpMRI CTB) followed by standard biopsy (SB) in the same setting by two different urologists. Diagnostic yield of biopsy cores, complications, and stage migration of Gleason’s grades was analyzed. RESULTS: Out of 75 patients, 34.6% had abnormal digital rectal examination (DRE), and the median serum PSA was 10.6 (4.5–20) ng/mL. Total MRI suspicious lesions were 163. Out of 1263 SB cores, 371 cores were positive for cancer (29.35%), and out of 326 mpMRI CTB cores, 120 were positive for cancer (36.8%) (P<0.0001). Histopathological examination (HPE) revealed 88%, 92%, and 100% clinically significant cancers in PIRADS 3, 4 and 5 lesions. SB and mpMRI CTB in combination have better cancer detection yield than either of the modality when used alone (P-<0.0001). Clavien-Dindo grade 1 and grade 4a complication were seen in 47 (62.6%) and three (4%) patients. CONCLUSION: In biopsy-naive men with suspected prostate cancer and equivocal DRE, the addition of pre-biopsy mpMRI detects greater numbers of people with clinically significant prostate cancer when compared with SB alone. Combining SB with mpMRI CTB has a superior diagnosing ability when compared with either of the biopsy modalities when used alone.